2011
DOI: 10.1097/ncm.0b013e3181f0555b
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Consultation for Case Managers in Community Mental Health

Abstract: Statistically significant differences in job satisfaction and perceptions of self-efficacy were found 18 months into the study, when case managers were more actively seeking occupational therapy consultation services and were reporting improved client outcomes from occupational therapy intervention. In addition, themes related to both positive and negative factors impacting the occupational therapy consultation program were identified and provided useful data for development of future consultation services. IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…The context of homelessness combined with health co-morbidities puts individuals at higher risk of cognitive impairment and decreased opportunity to use and develop functional skills (Burra et al, 2009;Helfrich & Synovec, 2019). Studies identifying valued occupations of homeless individuals revealed varied priorities and goals, with attention to survival, identity and social connectedness, and self-care (Chapleau et al, 2011;Illman et al, 2013;Marshall et al, 2017;Muñoz et al, 2006;Salsi et al, 2017;Thomas et al, 2017). This population can benefit significantly from access to occupational therapy in order to develop functional living skills, address underlying cognitive deficits, increase self and health management skills, and to more easily transition to and maintain independent living through occupational engagement (Gutman & Raphael-Greenfield, 2017;Helfrich & Fogg, 2007;Roy et al, 2017;Thomas et al, 2017).…”
Section: Literature Review Occupational Therapy and Homelessnessmentioning
confidence: 99%
See 2 more Smart Citations
“…The context of homelessness combined with health co-morbidities puts individuals at higher risk of cognitive impairment and decreased opportunity to use and develop functional skills (Burra et al, 2009;Helfrich & Synovec, 2019). Studies identifying valued occupations of homeless individuals revealed varied priorities and goals, with attention to survival, identity and social connectedness, and self-care (Chapleau et al, 2011;Illman et al, 2013;Marshall et al, 2017;Muñoz et al, 2006;Salsi et al, 2017;Thomas et al, 2017). This population can benefit significantly from access to occupational therapy in order to develop functional living skills, address underlying cognitive deficits, increase self and health management skills, and to more easily transition to and maintain independent living through occupational engagement (Gutman & Raphael-Greenfield, 2017;Helfrich & Fogg, 2007;Roy et al, 2017;Thomas et al, 2017).…”
Section: Literature Review Occupational Therapy and Homelessnessmentioning
confidence: 99%
“…In the United States, there is a growing consensus in the profession that occupational therapy can have a significant role on interdisciplinary teams in integrated primary care settings serving clients with complex chronic conditions (Pape & Muir, 2019;Winship et al, 2019). There is limited research, however, on the role of occupational therapy in primary and integrative health care, especially on the impact on clients or contributions to the interdisciplinary treatment team (Chapleau et al, 2011;Dahl-Popolizio et al, 2016;Koverman et al, 2017). There have been many studies promoting efficacious community practice through integrated health delivery models, such as FQHCs, in which care for those with chronic, complex conditions is coordinated and delivered by a consistent group of providers, indicating a benefit to co-location of occupational therapy services in community settings (Dubuc et al, 2013;Ellis & Alexander, 2016;Engineer et al, 2015;Montenegro et al, 2011;Rumball-Smith et al, 2014).…”
Section: Occupational Therapy and Integrated Primary Carementioning
confidence: 99%
See 1 more Smart Citation
“…The founders of occupational therapy were from various disciplines, including medicine, nursing, architecture, and social work (Quiroga, 1995), so by nature of occupational therapy's founding circumstances, the profession recognizes and values collaboration. Chapleau, Seroczynski, Meyers, Lamb, and Haynes (2011) noted that occupational therapy adds valuable contributions to team outcomes because it includes "services for health promotion, including self-care management, cognitive assessments, activity-based programming, and home safety evaluation and modification" (p. 71).…”
Section: Case Management Concepts: Collaboration and Client Engagementmentioning
confidence: 99%
“…Anecdotally, compensation for case managers typically is not competitive with traditional compensation for occupational therapy practitioners, who generally are paid more than nurses and social workers (Bureau of Labor Statistics, 2015). However, occupational therapy practitioners are frequently sought out to consult with case managers because of their expertise in understanding how people function in their homes and communities and perform independently at home, work, and school (Chapleau et al, 2011). Occupational therapy practitioners must take advantage of opportunities to consult and thus promote the broader case management skills they possess to further interdisciplinary knowledge and awareness of occupational therapy.…”
Section: Case Management and Care Coordination Positions And Rolesmentioning
confidence: 99%